Pengaruh Orientasi Pasar Terhadap Kinerja Perusahaan Dengan Komitmen Organisasi Dan Kemampuan Pemasaran Sebagai Variabel Mediasi (Studi Empiris Pada Perusahaan Sektor Ritel Di DKI Jakarta) - Ongky Alex Sander (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research aims to determine the impact of market orientation and company performance with organisational commitment and marketing capabilities as a mediation variables. This research is conducted in retail business sector in DKI Jakarta. The researcher collect the data by using questionnaire technique with  95 respondents which have position at least as a supervisors. In collectiong the sample, the researcher uses purposive sampling and SMARTPLS 2.0 M3 as a statistical tool for processing the data. The results of data processing to explain the significant effect between market orientation to organisational commitment, marketing capabilities,  and company performance. Organisational commitment and marketing capabilities has significant impact to company performance. As well as organisational commitment and marketing capabilities have a mediating role on corporate performance but both of the as partial mediation.